The correlation of non-motor symptoms and sleep on balance in Parkinson's disease patients with normal cognition and mild cognitive impairment - Sarıcaoğlu, Mevhibe; Helvacı Yılmaz, Nesrin; Özer, Fahriye Feriha; Hanoğlu, Lütfü (Springer London Ltd, 2021)
Background Parkinson's disease (PD) is characterized by non-motor symptoms (NMS) as well as by motor symptoms. Together with the impairment of cognitive functions, NMS and sleep also affect motor symptoms negatively. The aim of our study is to examine the correlation of NMS and sleep on balance in PD patients with normal cognition (PD-NC) and with mild cognitive impairment (PD-MCI). Methods A total of 69 patients were included in our study. Using the Standardized Mini-Mental State Examination, participants were divided into 2 groups, PD-NC and PD-MCI. Patients were assessed with the Unified Parkinson's Disease Rating Scale (UPDRS), the Berg Balance Scale (BBS), the Tinetti Balance Assessment Tool (TBAT), the Non-Motor Symptoms Questionnaire (NMSQ), and the Parkinson's Disease Questionnaire (PDQ-39). Results PD-MCI patients had statistically significant worse motor symptoms and more balance disorder compared to PD-NC (UPDRS: p = 0.009; BBS: p = 0.010; TBAT: p = 0.004). PD-MCI patients had greater severity of non-motor symptoms and worse sleep quality than the PD-NC group (NMSQ-total: p = 0.02; NMSQ-sleep total: p = 0.01). The evaluation has shown that with a diagnosis of MCI, NMS, and sleeping problems were correlated, and the correlation was associated with impairment of the balance function. While being more pronounced in the PD-MCI group, quality of life was affected in both groups (p < 0.05). Conclusion Our data demonstrate a negative effect on the balance function in patients with cognitive impairment suffering increased NMS and sleeping disorders. Treatment of these patients needs to concentrate on NMS and cognitive functions as much as on motor symptoms.
Keywords: Balance; Mild Cognitive Impairment; Non-Motor Symptoms; Parkinson’s Disease; Sleep